Tax Aggressiveness Seen From Company Characteristics and Corporate Social Responsibility - Yunus Harjito; Christin Novita Sari; - Yulianto (Master of Accounting Universitas Trunojoyo Madura, 2017)
This study aims to analyze the effect of company characteristics and Corporate Social Responsibility on tax aggressiveness. Dependent variable used in this research was tax aggressiveness as measured by effective tax rate. The independent variables in this study were company characteristics consisting firm size, leverage, and capital intensity. This study also used Corporate Social Responsibility as independent variable. The sample was 41 companies with the research period for 5 years (2011-2015) selected by using purposive sampling method. The data analysis in this study used multiple linear regression to obtain a comprehensive picture of the effect of corporate characteristics and Corporate Social Responsibility on Tax Aggressiveness using SPSS version 21 for Windows. The result shows that company size and capital intensity significantly affect the tax aggressiveness. However, two other variables (leverage and Corporate Social Responsibility) that allegedly affect tax aggressiveness are not proven to affect tax aggressiveness.